Rutherford-en esperimentua / diseinu nagusia , Amy Hanson, San McKagan; software-garapena, Jesse Greenberg ...[et al:]; [itzulpena, Inma Zufiria] - Hanson, Amy; McKagan, Sam; Greenberg, Jesse; Zufiria Unanue, Inma
Rutherford-en esperimentua ulertzeko simulazio interaktiboa.